Laser spectroscopy of the $$^2S_{1/2}{-}^2P_{{1}/2}$$ 2 S 1 / 2 - 2 P 1 / 2 , $$^2P_{3/2}$$ 2 P 3 / 2 transitions in stored and cooled relativistic C $$^{3+}$$ 3 + ions - D. Winzen (Nature Portfolio, 2021)
Abstract The $$^2S_{1/2}{-}^2P_{{1}/2}$$ 2 S 1 / 2 - 2 P 1 / 2 and $$^2S_{1/2}{-}^2P_{{3}/2}$$ 2 S 1 / 2 - 2 P 3 / 2 transitions in Li-like carbon ions stored and cooled at a velocity of $$β ≈ 0.47$$ β ≈ 0.47 in the experimental storage ring (ESR) at the GSI Helmholtz Centre in Darmstadt have been investigated in a laser spectroscopy experiment. Resonance wavelengths were obtained using a new continuous-wave UV laser system and a novel extreme UV (XUV) detection system to detect forward emitted fluorescence photons. The results obtained for the two transitions are compared to existing experimental and theoretical data. A discrepancy found in an earlier laser spectroscopy measurement at the ESR with results from plasma spectroscopy and interferometry has been resolved and agreement between experiment and theory is confirmed.